ANALISIS KELENGKAPAN PENGISIAN DOKUMEN REKAM MEDIS RAWAT INAP DI RUMAH SAKIT : LITERATURE REVIEW - Endah Widaningtyas; Fadzli Melani Fitri; Roro Kushartanti; Andri Asmorowati (STIKES HAKLI Semarang, 2022)
Abstract The completeness of filling out the medical record file must reach 100% for 1x24 hours after the patient leaves the hospital. The purpose of this study was to determine the completeness of filling in inpatient medical record documents.This research method is a literature review regarding the completeness analysis of filling out inpatient medical record documents in hospitals. Literature is obtained from searching through an online database, namely Google Scholar. Based on the results of the study, it was found that the completeness of filling out inpatient medical record documents at the hospital for patient identification there were still 3 articles with a percentage of 30%, the completeness of filling out important reports on the patient's DRM there were still 4 articles with a percentage of 40%, completeness of authentication on the patient's DRM was still there. Two articles with a percentage of 20%, and the completeness of the correct documentation is still 1 journal with a percentage of 10% which is said to be still not good, because the number of completeness of filling out medical record documents has not reached 100%. Suggestions for further research It is hoped that this documentation study will be developed and compared with other studies. And the method used is related to the limitations of researchers on data collection in the field due to Covid-19. Keywords : Analysis, Completeness, Medical Record Documents, Hospitalization Abstrak Kelengkapan pengisian berkas rekam medis harus mencapai 100% selama 1x24jam setelah pasien keluar rumah sakit. Tujuan Penelitian ini adalah untuk mengetahui kelengkapan pengisian dokumen rekam medis rawat inap. Metode penelitian ini adalah studi literature (Literature Review) mengenai analisis kelengkapan pengisian dokumen rekam medis rawat inap di rumah sakit. Literature diperoleh dari penelusuran melalui database online yaitu Google Scholar. Berdasarkan hasil penelitian diketahui bahwa Kelengkapan pengisian dokumen rekam medis rawat inap di rumah sakit pada identitifikasi pasien masih ada 3 jurnal dengan presentase 30%, kelengkapan pengisian laporan penting pada DRM pasien masih ada 4 artikel dengan presentase 40%, kelengkapan autentifikasi pada DRM pasien masih ada dua artikel dengan presentase 20%, dan kelengkapan pendokumentasian yang benar masih ada satu artikel dengan presentase 10% yang dikatakan masih kurang baik, karena angka kelengkapan pengisian dokumen rekam medis masih belum mencapai 100%. Diharapkan untuk dapat mengembangkan studi dokumentasi ini dan membandingkan dengan studi lainnya. Serta metode yang digunakan terkait keterbatasan peneliti terhadap pengambilan data dilapangan akibat Covid-19. Kata Kunci : Analisis, Kelengkapan, Dokumen Rekam Medis, Rawat Inap